A Note on the Working Qualities of some Indian Timbers - Rawat, B. S.; Rajput, S. S.; Pant, B. C. (Indian Forester, 1972)
Briefly surveying the work done on evaluation of working qualities of Indian timbers so far, the method of testing and evaluation followed for the present study has been described. Working qualities of four species viz. Tectona grandis, Adina cordifolia, Mangifera indica and Terminalia myriocarpa have been given under four major operations namely planing, turning, boring and mortisting.